OPTIMALISASI PEMBELAJARAN BAHASA INGGRIS DENGAN CANVA DAN QUIZIZZ: PENGABDIAN KEPADA MASYARAKAT DI SMPK TARUNA HARAPAN BANGSA-JAKARTA - Hendrikus Male; Nel Bryan C. Tugelida; Johannes Eric Joseph; Risantha Anache Abigail Samuel; Debora Sabrina; Julio Maurits Bao (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
This community service program aimed to enhance motivation and competence in learning English through the use of digital platforms: Canva and Quizizz. The activity introduced students to the effective use of these two tools to support English language learning in an engaging and student-centered environment. The program included presentations, hands-on workshops, and interactive quizzes that emphasized the integration of creative design and gamified assessment. A total of 23 students participated in the evaluation at the end of the program through a questionnaire consisting of 15 items on a four-point Likert scale. The results of the evaluation showed overwhelmingly positive responses. Over 90% of students either agreed or strongly agreed that Canva and Quizizz increased their motivation, enhanced their understanding of the material, and made learning more enjoyable. Canva helped students create visually appealing content while also aiding vocabulary retention, and Quizizz contributed to improved confidence and engagement during assessments. Furthermore, the majority of students believed that these tools improved their English skills and supported more effective, independent learning. These findings demonstrate that integrating digital learning platforms such as Canva and Quizizz not only enhances the quality of English instruction but also positively influences students' attitudes, motivation, and participation.